KEBIASAAN BELAJAR BAHASA ARAB SISWA KELAS UNGGULAN (PENELITIAN ETNOGRAFI DI MTSN BATUSANGKAR TP. 2011/2012) - NURLAILA NURLAILA (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2012)
his study aimed at identifying, describing and understanding students’ learning habit at school and at home as well, and figuring out contributing factors in establishing and developing their habits. This study employed ethnography method and such techniques as observation, interview, documentary studies and questionnaire. The obtained data were analyzed by means of domain, taxonomy and componential analyses. Findings showed that the learning habits of the majority students of outstanding achievement class (kelas unggulan) of MTsN Batusangkar both at school and at home were good. Those habits were in line with achievement which they took is a reward. Satisfaction toward the reward encouraged them to be more motivated in learning which in turn developed better learning habit. These had formed a good chain in learning process. Factors that contributed to the establishment and development of learning habit were internal (self motivation, management, direction and development) and external factors (social and instrumental environments).Kata kunci: siswa, kebiasaan belajar, bahasa Arab, kelas unggulan